The Shadow of Your Smile - Clark, Mary Higgins (New York Simon & Schuster Audio, 2010)
Olivia Morrow, old and in failing health, must choose whether or not to reveal an explosive family secret--that her deceased cousin Catherine, a nun being considered for beatification by the Catholic Church, gave birth to a child and gave him up for adoption.
Unabridged.
Compact discs.
Keywords: Family secrets -- Fiction; Inheritance and succession -- Fiction; Audiobooks; Suspense fiction